MulSeMaker: An MDD Tool for MulSeMedia Web Application Development - Sousa, Marcelo Fernandes de; Ferraz, Carlos André Guimarães; Kulesza, Raoni; Ayres, Italo; Lima, Matheus (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
MulSeMedia applications aim to stimulate other human sensory receptors such as mechanoreceptors, chemoreceptors and thermoreceptors. They increase the degree of immersion of users as well as improve the Quality of Experience and are standardized by MPEG-V. It is currently possible to identify a gap in the definition of processes, methods and tools to support the systematic development of MulSeMedia applications. This paper presents a tool called MulSeMaker for the development of MulSeMedia applications in the Web domain. It was developed based on the application family concept from the Generative Software Development. In order to investigate evidence to confirm the benefits of the proposed tool, empirical studies were carried out to collect and analyze qualitative and quantitative data.